Paediatric sarcoidosis. (February 2019) - Nathan, Nadia; Sileo, Chiara; Calender, Alain; Pacheco, Yves; Rosental, Paul-André; Cavalin, Catherine; Macchi, Odile; Valeyre, Dominique; Clement, Annick; ,; ,
Summary: Paediatric sarcoidosis is an extremely rare disease characterized by a granulomatous inflammation. The estimated incidence is 0.6–1.02/100, 000 children, but in the absence of international registers, the disease is probably under-reported. Its pathophysiologic basis is not clearly understood but the current hypothesis is a combination of a genetic predisposition and an environmental exposure that could be either organic or mineral. Contrary to adult forms of the disease, general symptoms are often at the forefront at diagnosis. In its most frequent form, paediatric sarcoidosis is a multi-organ disorder affecting preferentially the lungs, the lymphatic system and the liver, but all organs can be affected. This review aims to provide an overview of current knowledge on sarcoidosis in children, providing a summary of the data available from cohort studies on the presentation, the management and the evolution of the disease in this specific population.